Selective Estrogen Receptor Modulators – turning point in therapy of menopause - J. Jakimiuk, Artur; Bogusiewicz, Michał (Menopause Review/Przegląd Menopauzalny, 2002)
Selective Estrogen Receptor Modulators (SERMs) are compounds, which reveal estrogenic or antiestrogenic activity, depending on target tissue. SERMs act through estrogen receptors. Their selectivity is associated with different affinity to estrogen receptors a and b, tissue distribution of both receptors as well as presence of transcription coactivators and corepressors in the cell. Tamoxifen, a SERM of first generation, since over 20 years is used in prevention and treatment of breast cancer. Recently, it has been proposed that reduction of drug dose may decrease the incidence of adverse events without loss of therapeutic efficacy. Raloxifene is the first SERM approved for prevention and treatment of postmenopausal osteoporosis. It prevents from vertebral fractures and increases bone mineral density. Moreover, the drug decreases the risk of breast cancer, beneficially affects lipoprotein metabolism and declines serum concentrations of arteriosclerosis markers.